Politics and Strategic Action: The Contribution of Political Consultants to PKS's Electoral Success in South Sulawesi - Syahril, Syahril; Alim, Irwan; Hawing, Hardianto (Journal of Contemporary Local Politics, 2024)
This study aims to analyze the strategies employed by Abdul Rahman in securing victory as a member of the South Sulawesi Provincial Legislative Council (DPRD) in Electoral District 4. The primary focus of this research is the role of political consultants as independent actors who formulate effective campaign strategies without being involved in other local political dynamics. Using a qualitative method with a descriptive approach, data was collected through interviews and documentation related to the campaign's implementation. The findings reveal that Abdul Rahman's success was supported by strategies emphasizing community-based approaches and strengthening political networks across three regencies: Bantaeng, Jeneponto, and the Selayar Islands. Political consultants played a crucial role in managing relevant local issues and effectively mobilizing mass support, without explicitly targeting specific competitors. By adopting a tailored approach that resonated with the unique socio-political dynamics of each region, Abdul Rahman successfully secured significant votes across all three areas. This study highlights the importance of political consultants in modern electoral campaigns, particularly in crafting strategies that align with local contexts and voter behavior. It also underscores the effectiveness of community-focused campaigns in building trust and garnering support, offering valuable insights for future political campaigns in similar contexts.